1999
DOI: 10.1111/j.1600-0714.1999.tb02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent cells in amalgam‐associated oral lichenoid contact lesions

Abstract: Inflammatory cells in amalgam‐associated, oral lichenoid contact lesions (OLL) were studied in 19 patients by immunocytochemistry using monoclonal antibodies. Ten of the patients displayed allergic patch test (PT) reactions to several mercury compounds and nine were negative. The immunocytochemical quantification showed a uniform composition of the inflammatory mononuclear cells in the two study groups. The number of HLA‐D/DR‐positive dendritic cells (P<0.001) and CD1a‐positive Langerhans cells (P=0.035) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
3
20
0
2
Order By: Relevance
“…The difference in mean LI among the study groups showed statistical significance. These observations were consistent with that of McCartan and Lamey,[4] Regezi et al .,[10] Laine et al .,[11] who reported statistically significant higher number of LC in LP. However they did not observe significant difference of CD1a LI between the different layers of the epithelium of LP.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in mean LI among the study groups showed statistical significance. These observations were consistent with that of McCartan and Lamey,[4] Regezi et al .,[10] Laine et al .,[11] who reported statistically significant higher number of LC in LP. However they did not observe significant difference of CD1a LI between the different layers of the epithelium of LP.…”
Section: Discussionsupporting
confidence: 93%
“…Mercury compounds may also cause musculoskeletal and neuropsychological symptoms (9). It has been proven that contact allergy to mercury is directly correlated with the incidence of oral lichen planus (5). The term 'oral lichenoid lesion' is commonly used to describe such lesions that develop as a consequence of dental restorations (1,5,9).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that contact allergy to mercury is directly correlated with the incidence of oral lichen planus (5). The term 'oral lichenoid lesion' is commonly used to describe such lesions that develop as a consequence of dental restorations (1,5,9). The clinical appearances and histopathologic changes associated with oral lichenoid lesions and oral lichen planus are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with biopsies showed increased mercury levels in the adjacent tissue and increased counts of mononuclear cells. These in- creased cell counts are believed to be associated with a type 4 allergic reaction in some patients and with an unspecific reaction of the immune system in others [125][126][127]. When amalgam is removed, the alterations of the oral mucous membranes are usually reversible [128][129][130][131].…”
Section: Hypersensitivity In Humansmentioning
confidence: 99%